Istro-Romanian Subjunctive Clauses - Corbeanu, Cătălina Ramona; Hill, Virginia (Languages (Basel), 2024)
This paper aims to define the featural composition of the complementizers that introduce subjunctive complements in Istro-Romanian, and to identify the internal organization of the subjunctive clause in terms of subject positions, verb movement, clitic placement and constituent fronting. In a nutshell, the observation is that the complementizer neca replaces se within the syntactic pattern of Old Romanian; that is, a pattern that displays intra- and inter-language variation with respect to the distribution of complementizers within the subjunctive CP. Tests of word order also indicate intra-language variation in the parametric settings for clitic placement (either high or low), for the argumental subject position (either in Spec,TP, yielding SVO, or in Spec,vP, yielding VSO) and for constituent movement under discourse triggers (either scrambling or fronting to CP).